Pengembangan Transaction Monitoring Pajak Berbasis IoT Dengan Fitur Script Auto Reboot Studi Kasus : PT. Pinisi Elektra - Hartini Hartini; Sri Primaini; Nurhayani Nurhayani; Sukro Nanda Darfero (Jurnal Informatika Global)
Online tax payments are one way to speed up the tax reporting process for taxpayers. The development of the online system is still often experiencing problems, especially the accumulation of data which eventually the online system experiences obstacles that result in the payment process being hampered. Another problem that may occur is that there are still many taxpayers who do not know and understand the online system properly. The development of transaction monitoring has a weakness where the computer system connection will die if it is used continuously to monitor transactions that occur within 1 or 2 weeks depending on the temperature conditions of the system in which it is placed. Therefore, it is necessary to add the auto reboot feature. The development of internet of things (IoT)-based tax transaction monitoring will make it easier for taxpayers to pay taxes because there is a link between taxpayers and companies engaged in tax payment services so that taxpayers are no longer bothered with the matter of paying taxes. The purpose of this study is to design an IoT-based transaction monitoring method and connect transaction monitoring tools to each cash register database or server in each store. While the method used in this research is data collection, among others in the form of observation and interviews as well as system development methods which include analysis, design, implementation, operation, and system maintenance. The results obtained from the design and connectedness of the system indicate that tax transaction monitoring can be carried out continuously so that the system can make it easier for taxpayers to carry out reporting. Keywords: online tax, taxpayers, transaction monitoring, auto reboot, internet of things